Protection of personal data under martial law in Ukraine - V. A. Svitlychnyi (Law and Safety)
The article is devoted to the issue of personal data protection under martial law in Ukraine. A detailed study of this issue has been carried out, aspects of the regulatory environment and levels of personal data protection in such difficult conditions have been considered.